Biallelic Mutations in Tetratricopeptide Repeat Domain 26 (Intraflagellar Transport 56) Cause Severe Biliary Ciliopathy in Humans. Issue 6 (20th February 2020) - Shaheen, Ranad; Alsahli, Saud; Ewida, Nour; Alzahrani, Fatema; Shamseldin, Hanan E.; Patel, Nisha; Al Qahtani, Awad; Alhebbi, Homoud; Alhashem, Amal; Al‐Sheddi, Tarfa; Alomar, Rana; Alobeid, Eman; et al.
Abstract : Background and Aims: The clinical consequences of defective primary cilium (ciliopathies) are characterized by marked phenotypic and genetic heterogeneity. Although fibrocystic liver disease is an established ciliopathy phenotype, severe neonatal cholestasis is rarely recognized as such. Approach and Results: We describe seven individuals from seven families with syndromic ciliopathy clinical features, including severe neonatal cholestasis (lethal in one and necessitating liver transplant in two). Positional mapping revealed a single critical locus on chromosome 7. Whole‐exome sequencing revealed three different homozygous variants in Tetratricopeptide Repeat Domain 26 ( TTC26 ) that fully segregated with the phenotype. TTC26 (intraflagellar transport [IFT] 56/DYF13) is an atypical component of IFT‐B complex, and deficiency of its highly conserved orthologs has been consistently shown to cause defective ciliary function in several model organisms. We show that cilia in TTC26 ‐mutated patient cells display variable length and impaired function, as indicated by dysregulated sonic hedgehog signaling, abnormal staining for IFT‐B components, and transcriptomic clustering with cells derived from individuals with closely related ciliopathies. We also demonstrate a strong expression of Ttc26 in the embryonic mouse liver in a pattern consistent with its proposed role in the normal development of the intrahepatic biliary system. Conclusions: In addition to establishing a TTC26 ‐related ciliopathy phenotype in humans, our results highlight the importance of considering ciliopathies in the differential diagnosis of severe neonatal cholestasis even in the absence of more typical features.